Adolescent sexual health education: Parents benefit too - Dinaj-Koci, Veronica (Health Educ Behav, 2015)
The inclusion of parents in adolescent-targeted interventions is intended to benefit the adolescent. Limited research has explored whether parents participating in these programs also directly benefit. We examined the impact of Caribbean Informed Parents and Children Together (CImPACT), the parenting portion of an adolescent-targeted HIV prevention intervention, on parent reported measures. Bahamian parent-youth dyads (N=1833) participating in the randomized control trial were assigned to receive one of four conditions. Parents were assessed longitudinally at baseline and 6 and 12 months later. Through 12 months follow-up, parents exposed to CImPACT showed higher knowledge of condom-use skills, perceptions of improved condom-use competence on the part of their youth, and perceived improved parent-child communication about sex-related information. Although youth were the targeted beneficiary, parents also directly benefited from the sexual risk reduction parenting program. Parents demonstrated improved perceptions and knowledge which would enable them to more effectively guide their child and also protect themselves from sexual risk.